The Effect of Information Technology on The Performance of MSMEs During the Covid-19 Pandemic - I Nyoman Nurcaya; I Ketut Rahyuda; Gusti Ayu Ketut Giantari; Ni Wayan Ekawati (International Journal of Social Science and Business, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are essential in improving a nation's economy. MSMEs can survive in a declining economic condition and also have the ability to absorb a large number of workers. However, the COVID-19 pandemic has had an impact on the global economy. This study aims to analyze the effect of information technology variables on the performance of MSMEs during the Covid-19 pandemic. This type of research is qualitative with a literature review approach. Several articles relating to information technology and MSME performance were used as references. The results obtained by MSMEs feel the positive impact of the role of information technology during the Covid-19 pandemic. Further research is expected to examine the role of information technology in the MSME sector. For example, SMEs in food, clothing, and others. SMEs must choose technology adaptations from the business activities and adjust to their existing financial capabilities. The government must help create adaptations for MSME actors during the Covid-19 pandemic, such as providing training and adequate technology infrastructure.